Pink manganian phengite in a high P/T meta-conglomerate from northern Syros (Cyclades, Greece) - Altherr, Rainer; Soder, Christian; Panienka, Sandra; Peters, Daniel; Meyer, Hans-Peter (Contributions to mineralogy and petrology, 2013)
A new occurrence of Mn-rich rocks was discovered within the high-pressure/low-temperature metamorphic rocks on the Palos peninsula of Syros (Greece). Near the summit of Mount Príonas, a meta-conglomerate consists of calcite (~63 wt%), pink manganian phengite, blue-purple manganian aegirine-jadeite, microcline, albite and quartz. In addition, it contains abundant braunite-rich aggregates (up to ~1.5 cm in diameter) that include hollandite [(Ba0.98-1.02K<0.01Na<0.02Ca<0.03) (Mn1.02-1.523+Fe0.38-0.883+Ti0.29-0.92Mn5.11-5.764+)O16], barite and manganian hematite. Due to metamorphic recrystallization and deformation, the contacts between clasts and matrix are blurred and most clasts have lost their identity. In back-scattered electron images, many aegirine-jadeite grains appear patchy and show variable jadeite contents (Jd10-67). These pyroxenes occur in contact with either quartz or albite. Manganian phengite (3.41-3.49 Si per 11 oxygen anions) is of the 3T type and contains 1.4-2.2 wt% of Mn2O3. At the known P-T conditions of high-pressure metamorphism on Syros (~1.4 GPa/ 470 °C), the mineral sub-assemblage braunite + quartz + calcite (former aragonite) suggests high oxygen fugacities relative to the HM buffer (+7 ≤ ∆fO2 ≤ + 17) and relatively high CO2 fugacities. The exact origin of the conglomerate is not known, but it is assumed that the Fe-Mn-rich and the calcite-rich particles originated from different sources. Braunite has rather low contents of Cu (~0.19 wt%) and the concentrations of Co, Ni and Zn are less than 0.09 wt%. Hollandite shows even lower concentrations of these elements. Furthermore, the bulk-rock compositions of two samples are characterized by low contents of Cu, Co and Ni, suggesting a hydrothermal origin of the manganese ore. Most likely, these Fe-Mn-Si oxyhydroxide deposits consisted of ferrihydrite, todorokite, birnessite, amorphous silica (opal-A) and nontronite. Al/(Al + Fe + Mn) ratios of 0.355 and 0.600 suggest the presence of an aluminosilicate detrital component.